VD_FINDINFO Jug / 2011 / 170 vom 23. Mai 2011 - VD Tribunal cantonal (2011)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT | 187 ch. 1 CP, 189 al. 1 CP, 197 ch. 1 CP, 40 CP, 43 CP, 51 CP, 63 CP, 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)